SURDOCEGOS E OS DESAFIOS NOS PROCESSOS SOCIOEDUCATIVOS: OS MEDIADORES E A TECNOLOGIA ASSISTIVA - VILELA, ELAINE GOMES (2018)
This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – Brasil (CAPES) – Finance code 001 – aims to show that throughout history, many deafblinds have been marked by practices of social exclusion that have reinforced inaccessibility to knowledge spaces. In this context, this research investigates the formative trajectory of deafblinds in the different levels of schooling, explaining the challenges in society to the detriment of exclusion. The objective is to understand what emerges when deafblinds reflect on the processes they have gone through, considering their uniqueness, from the linguistic acquisition of forms of communication developed according to their needs, in addition to the assistive technology resources used. In this perspective of the school as a propitious place of social development, some questions are present: How does communication and socialization occur? What pedagogical practices can be used? What assistive technology resources favor the promotion of teaching learning? What is the importance of the mediator in communication? From the theoretical point of view, some references are cited, among them: McInnes and Therffry (1997), Bertoni and Ferioli (1995), Baldwin (1997), Galvão (2010), Maia (2004), Cader-Nascimento (2006) and Watanabe (2017). This study is based on the qualitative exploratory approach, in the mode of narrative research developed by Clandinin and Connelly (2015), in the autobiographical perspective based on the perceptions of Ferrarotti (2010), Josso (2010) and Creswell (2010). The research presents the formation of a link between the researcher and the participants, a factor that facilitated the exchange of experiences. Here is the path of language acquisition by Helen Keller, a world-known deafblind woman, and then a brief description of the etiology of deafblindness. The study offers possibilities for attending and reflections on legal guidelines that favor access to education, as well as to cite facilitating strategies and assistive technology resources. The use of the remaining sensory senses, the forms of communication among them the haptic social communication, the mediators and the family performance are approached from the narratives of the participants' experiences. The results show that it is necessary to look sharply at the needs and the possibilities, highlighting the importance of building the link for effective service. Among other aspects, the study reveals the lack of research in the area of deafblindness in relation to guiding-interpretation techniques and the use of haptic social communication. However, a different study is beginning here, opening the frontiers for future discussions, instigating researchers that add to this field of knowledge.